NM441, penetration in saliva and effusion level of tooth extraction wounds - Yamazaki, Junko; Sasaki, Jiro; Karakida, Kazunari (Japanese Journal of Chemotherapy, 1996)
We performed pharmacokinetic studies on NM441, a new quinolone, in the field of dentistry and oral surgery. 1) NM441 was administered to 10 healthy subjects before and after meal at 200mg, and the serum and the saliva concentrations of NM394 (an active form of NM441) were determined periodically. A pharmacokinetic study was performed using a one-compartment model. The parameters of pharmacokinetic analysis were as follows. Serum Saliva Fasting Non-fasting Fasting Non-fasting Tmax(h) 0.85 1.52 2.23 2.38 Cmax(μg/ml) 1.02 0.82 0.19 0.19 T1/2(h) 2.73 3.47 3.05 3.24 AUC(μg·h/ml) 4.45 4.66 0.97 1.00 2) NM441 200mg was administered to 40 patients and the effusion of tooth extraction wounds of NM394 was measured when tooth was extracted. At 1-5 hour after administration, the concentration in the effusion of NM394 revealed 0.15-0.97μg/ml.